Virtual element method on polyhedral meshes for bi-harmonic eigenvalues problems. (1st September 2022) - Dassi, Franco; Velásquez, Iván
Abstract: In this paper we study a C 1 Virtual Element Method (VEM) on polyhedral meshes for bi-harmonic eigenvalue problems in three dimensions. Optimal order error estimates for the eigenfunctions and a double order for the eigenvalues are obtained by using the approximation theory of compact self-adjoint operators. Finally, a set of tests will numerically prove the theoretical result of the proposed scheme.